2018
DOI: 10.1016/j.jvs.2017.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of abdominal aortic aneurysms with narrow aortic bifurcation using Excluder bifurcated stent grafts

Abstract: Abdominal aortic aneurysms with narrow bifurcation can be treated with the bifurcated Excluder device without additional adjunctive measures. The presence of limb stenosis during follow-up is not associated with occlusion. Long-term follow-up studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It seems intuitive that a narrow distal aorta would result in decreased blood flow to the extremities and a higher incidence of these comorbidities. However, an increased rate of hypertension or peripheral vascular disease in narrow AOB patients was not observed in the studies reported by Marques De Marino et al 15 and Troisi et al 14 and would be an interesting area of future exploration.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It seems intuitive that a narrow distal aorta would result in decreased blood flow to the extremities and a higher incidence of these comorbidities. However, an increased rate of hypertension or peripheral vascular disease in narrow AOB patients was not observed in the studies reported by Marques De Marino et al 15 and Troisi et al 14 and would be an interesting area of future exploration.…”
Section: Discussionmentioning
confidence: 82%
“…A recent single-center study in Spain reported on a 10-year experience with the EXCLUDER device in 232 patients, 53 of whom had narrow AOBs. 15 The authors found that a narrow AOB is a risk factor for later limb stenosis, although in their experience, limb stenosis was not found to be associated with later limb occlusions (of which there were none through 37 months). Variance in ratio of stent limb diameter to AOB diameter was found to be, by far, the greatest risk factor for later limb stenosis.…”
Section: Discussionmentioning
confidence: 87%
“…Bifurcated stent grafts (BSG) have been widely used in endovascular aneurysm repair (EVAR) for treating patients with abdominal aortic aneurysms (AAAs) [ 1 ]. During the EVAR procedure, BSG deployment becomes even more complicated and time-consuming if patients have abnormal AAA features; for example, the aneurysm neck is unfavorable, or the common iliac arteries are highly splayed [ 2 ].…”
Section: Introductionmentioning
confidence: 99%